2013
DOI: 10.1186/1880-6805-32-15
|View full text |Cite
|
Sign up to set email alerts
|

Physiological relaxation induced by horticultural activity: transplanting work using flowering plants

Abstract: BackgroundDespite increasing attention and a growing volume of research data, little physiological evidence is available on the benefits of horticultural activity and the different effects on individuals. Therefore, the aim of the present study was to investigate the physiological effects of horticultural activity and to examine how differences in personality alter these effects.ResultsThe effects of transplanting real flowers (horticultural activity) and handling artificial flowers (control activity) on human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In this study, the value of log[LF/(LF + HF)] (corresponds to sympathetic activity) increases soon after the subjects start the tasks (either the transplanting or computer task), then shows a tendency for a slow decrease during the transplanting task, despite a consistent increase during the computer task. The stress-reducing effect was observed at the end of the transplanting task (the last 3 min); this finding may be partly consistent with that of a previous study [ 22 ]. However, this finding is on the basis of comparison with a computer task, a type of mental task, which tends to increase sympathetic nervous activity [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the value of log[LF/(LF + HF)] (corresponds to sympathetic activity) increases soon after the subjects start the tasks (either the transplanting or computer task), then shows a tendency for a slow decrease during the transplanting task, despite a consistent increase during the computer task. The stress-reducing effect was observed at the end of the transplanting task (the last 3 min); this finding may be partly consistent with that of a previous study [ 22 ]. However, this finding is on the basis of comparison with a computer task, a type of mental task, which tends to increase sympathetic nervous activity [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Compared with artificial flowers, real flowers significantly decreased sympathetic nerve activity. This result resembles that reported by a previous study on chrysanthemum transplantation for male university students with the Type A behavior pattern [ 27 ]. In contrast, some previous studies have reported increased parasympathetic nerve activity in addition to decreased sympathetic nerve activity, e.g., when viewing a forest environment in a sitting position [ 29 , 31 , 33 , 34 ] and following visual stimulation of high school students with fresh roses [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, they used indoor reading as a control, which may compromise broad interpretation of the results. A study of fresh chrysanthemum transplantation [ 27 ] revealed no significant differences among subjects; however, the authors indicated significant differences according to personality classifications, which we believe was a limitation.…”
Section: Introductionmentioning
confidence: 69%
“…However, van den Berg and Custers [ 16 ] used indoor reading as a control, which we considered inappropriate. In the study by Lee et al [ 34 ], there were no significant differences among subjects, and the authors indicated significant differences in cases of classification by personality, which we think was a limitation in that study. In evaluations of various horticultural therapies, physiological evaluations, such as HRV and heart rate, will be primarily required in the future from the perspective of evidence-based medicine; however, psychological evaluations should also be performed.…”
Section: Discussionmentioning
confidence: 63%
“…The main previous relaxation studies of horticultural products used the questionnaire evaluation. There have been a few reports regarding physiological relaxation effects [ 16 , 34 ]. However, van den Berg and Custers [ 16 ] used indoor reading as a control, which we considered inappropriate.…”
Section: Discussionmentioning
confidence: 99%